Muhammad : A Prophet for Our Time - Armstrong, Karen 1944- (London Harper Perennial, 2006)
A concise, balanced and illuminating portrait of this revered figure. Through comparison with other prophets and mystics she examines Muhammad's spiritual ideas, and uses the facts of his life - from which Muslims have drawn instruction for centuries - to make the tenets of Islam clear and accessible for readers of all faiths.
Include Glossary and Notes
Keywords: Muḥammad, Prophet, -632 -- Islam